ANALISIS DAMPAK APLIKASI E-TOURISM SEBAGAI MEDIA PROMOSI PARIWISATA TERHADAP KUNJUNGAN WISATAWAN KABUPATEN TANGGAMUS - Mar’atus Sholehah (STMIK Pringsewu, 2019)
The world of tourism is not new for everyone. Tourism has become an industry in every tourist destination. Various facilities and conveniences and entertainment provided to support various tourism activities have been provided by the government or other tourism supporting components. One of the facilities that can be developed is e-tourism. E-tourism can provide tourist destination information with various needs and supporting facilities for users, especially tourists. Services are provided through the website as a form of convenience that can be obtained by visitors. Implementation of e-torism applications has a very good impact on tourists in the process of obtaining information. In addition to having an impact on tourists, this application has an impact on local governments in an effort to increase the number of visitors. Based on the results of the study the number of tourists rose to 40%. Thus this application has a very good impact on the development of tourism potential in Tanggamus Regency.